Use of 30-Hz Accelerated iTBS in Drug-Resistant Unipolar and Bipolar Depression in a Public Healthcare Setting: A Case Series - Cantù, Filippo; Schiena, Giandomenico; Sciortino, Domenico; Di Consoli, Lorena; Delvecchio, Giuseppe; Maggioni, Eleonora; Brambilla, Paolo (Frontiers in Psychiatry, 2022)
Background: Depressive episodes, especially when resistant to pharmacotherapy, are a hard challenge to face for clinicians and a leading cause of disability worldwide. Neuromodulation has emerged as a potential therapeutic option for treatment-resistant depression (TRD), in particular transcranial magnetic stimulation (TMS). In this article, we present a case series of six patients who received TSM with an accelerated intermittent theta-burst stimulation (iTBS) protocol in a public healthcare setting. Methods: We enrolled a total number of six participants, affected by a treatment-resistant depressive episode, in either Major Depressive Disorder or Bipolar Disorder. Patients underwent an accelerated iTBS protocol, targeted to the left dorsolateral prefrontal cortex (DLPFC), three-week-long, with a total of 6 days of overall stimulation. On each stimulation day, the participants received 3 iTBS sessions, with a 15-minute pause between them. Patients were assessed by the Hamilton Rating Scale for Depression (HAM-D), the Montgomery-Asberg Depression Rating Scale (MADRS), the Hamilton Rating Scale for Anxiety (HAM-A), and the Mania Rating Scale (MRS). At baseline (T0), at the end of the second week (T1), and at the end of the cycle of stimulation (T2). Results: The rANOVA statistics showed no significant effect of time on the rating scale scores, with a slight decrease in MADRS scores and a very slight increase in HAM-A and HAM-D scores. No manic symptoms emerged during the entire protocol. Conclusions: Although accelerated iTBS might be considered a less time-consuming strategy for TMS administration, useful in a public healthcare setting, our results in a real-word six-patient population with TRD did not show a significant effect. Further studies on wider samples are needed to fully elucidate the potential of accelerated iTBS protocols in treatment-resistant depression.